THE METHOD OF GLOBAL READING FROM AN INTERDISCIPLINARY PERSPECTIVE - Vedran Dizdarevikj (My University, 2018)
Primary literacy in Macedonian education is in decline. This assertion has been proved both by the abstract theory, and by the concrete empirical data. Educational reforms in the national curriculum are on their way, and the implementation of the method of global reading is one of the main innovations. Misunderstanding of this method has led it its being criticized as a foreign import and as unnatural and incongruous for the specificities of the Macedonian language. We think that this argument is wrong. That is why this paper is going to extrapolate and explain the method of global learning and its basis in pedagogy, philosophy, psychology, anthropology and linguistics. The main premise of this paper is the relation of the part to the whole, understood from the different perspectives of philosophy, psychology, linguistics and anthropology. The theories of Kant, Cassirer, Bruner, Benveniste and Geertz are going to be considered in the context of the part – whole problem, by themselves, and also in their relation to the method of global reading.
Keywords: global reading, primary literacy, language, education, interdisciplinary